Optimasi Akses Informasi Sekolah Negeri Pao-Pao melalui Pengembangan Website Interaktif - Fadhil Irlan; Surianto Mappangara (Sakura Digital Nusantara, 2023)
At SDN Pao-Pao Makassar the process of conveying and obtaining information is carried out in the same way as usual, namely by waiting and having to come directly to school. To solve this problem, the author has a desire to make it easier for teachers, students or parents/guardians of students to know and convey school information. So the solution to this problem is to build a school information system website that can be accessed via the internet. The existence of this website can make it easier for teachers, students and parents/guardians of students to find school information quickly and practically. The mechanism of this information system is that the administrator manages and regulates the course of the school information system, the teacher manages the learning outcomes of students, while students or parents/guardians of students can see the results of student learning activities. Meanwhile, visitors can only see information about the school. The analysis and design tools used in the development of this website are system development methodologies, namely Use Case Diagrams. The information provided by SDN Pao-Pao using the internet is expected to make it easier for the general public to obtain up to date information.